Beneath the rhythm: Deciphering the subtle perforation of the right ventricle by a pacemaker lead - Kalyan Munde; Mohan Paliwal; Akshat Jain (Heart India)
Cardiac perforation by the lead of permanent pacemaker implantation devices is a critical complication that often occurs within 24 h after the implantation but can occur later. Here, we report a case of an 82-year-old female patient with perforation of the right ventricular wall due to right ventricle lead after 3 months of pacemaker implantation, which was managed conservatively.